Isolation And Characterization of Host-Associated Bacillus Spp. As Probiotics for Enhancing Fish Growth and Water Quality (Bioresearch Communications, 2026)
Incorporating Bacillus probiotics into feed can yield additional benefits, including enhanced growth and production in aquaculture. However, study did not receive much attention on enriched feed with host-associated Bacillus spp. isolated from the fish gut. Therefore, this study was conducted to isolate Bacillus spp. from the tilapia gut and to evaluate their probiotic potential for the growth of Nile tilapia (Oreochromis niloticus) and water quality parameters. Bacterial strains were isolated from tilapia guts using Bacillus selective media and then were identified by MALDI-TOF mass spectrometry and 16S rRNA gene sequencing. Probiotic potential was evaluated based on pH (2.5) and bile (0.5%) tolerance, extracellular enzyme production, and antibiotic susceptibility profiling. A total of 16 bacterial strains were isolated; of them, two were identified as Bacillus pumilus and Bacillus subtilis. Both survived in low pH and high bile concentration; showed extracellular protease and amylase activity; and had high susceptibility to most of the selected antibiotics. A 60-day in vivo experiment was conducted under three treatments: control (without probiotics); T2H (B. pumilus); and T2B (B. subtilis). A significant difference (p < 0.05) was observed among three treatments regarding weight gain (WG; g), average daily gain (ADG; g/day), and specific growth rate (SGR; %/day). Remarkably, the highest WG, ADG, and SGR values were estimated in T2B compared to T2H and control. Additionally, T2B exhibited significantly (p < 0.05) increased nitrate level compared to T2H and control. This study indicated that host-associated B. pumilus and B. subtilis could be the potential probiotics for O. niloticus.Bioresearch Commu. 12(2): 2137-2147, 2026 (January)